The Role of NS1 Gene Mutations in Dengue Virus Serotype 2 and Their Association with Clinical Severity of Dengue Hemorrhagic Fever: A Systematic Review - Nyoman Cahyadi Tri Setiawan; Rozikin Rozikin (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2025)
NS1 gene of Dengue Virus Serotype 2 (DENV-2) plays a significant role in the pathogenesis and clinical severity of dengue infections, including Dengue Hemorrhagic Fever. Mutations in the NS1 gene of DENV-2 are closely associated with the clinical severity of dengue. Methods: This review article employs a systematic review methodology, utilizing Scopus, PubMed and Web of Science from 2015 to 2025. Results: The T164S mutation was consistently associated with increased severity through elevated secreted NS1 (sNS1) production, complement activation, and inflammation. Conversely, the S103T mutation appeared in milder cases. NS1 mutations also correlated with immune hyperactivation, vascular leakage, and, in some cases, neurological symptoms such as encephalitis. Despite these findings, direct causality between specific mutations and clinical outcomes requires further investigation. Conclusion: Mutations in the NS1 gene of DENV-2 affect the stability, secretion, and immunogenic properties of the NS1 protein, leading to increased vascular leakage and severe disease outcomes